Student Brawls: How Do Police Prevent and Take Action on Them? - Fenia Mulyasari (Advances in Police Science Research Journal, 2021)
The rise of brawl cases between students in the jurisdiction of the Bogor City Police has made the people of Bogor City nervous. What is done by students who do brawl is very detrimental to society. The danger carried out by the perpetrators of the brawl made the police take efforts to prevent the occurrence of brawls between high school students, the Bogor City Police Binmas Unit in an effort to prevent this from doing outreach to schools with the aim of the researcher being to describe and analyze the problem formulation. This research was conducted in Bogor City Police using a qualitative approach. With the field research method, the purpose of this study is to find out how the extension activities of the Bogor City Police Binmas Unit in preventing the occurrence of brawls between high school students in the legal area of ​​the Bogor City Police. The results of this study indicate that the efforts made by the Binmas Unit in conducting counseling to schools have gone well. Extension activities have been carried out but not all schools receive counseling. As a result, brawls between students are still occurring and recurring. Based on the findings of this study, it is concluded that in the future, there will be plans for activities carried out by the Binmas Unit at schools in order to increase the intensity of outreach activities targeting high school students.